ABCB5 expression and cancer stem cell hypothesis in oral squamous cell carcinoma - Grimm, Martin; Krimmel, Michael Fred; Polligkeit, Joachim; Hoffmann, Jürgen (European journal of cancer, 2012)
Introduction: The vast majority of oral cancers are squamous cell carcinomas (OSCC). The effectiveness of adjuvant cytostatic chemotherapy for OSCC is frequently restricted due to an inducible cellular mechanism called multidrug resistance (MDR) and a putative cancer stem cell (CSC) compartment in human carcinogenesis expressing multidrug efflux pumps. The novel human ATP-binding cassette (ABC) transporter ABCB5 [subfamily B (MDR/TAP) member 5] acts as an energy-dependent drug efflux transporter and marks tumour cells of a putative CSC compartment. However, to date, there is no link between ABCB5 expression and OSCC. Materials and methods: Expression of ABCB5 was analysed in OSCC specimen (n=191) and cancer cell lines (BICR3, BICR56) by immunohistochemistry, real-time polymerase chain reaction (RT-PCR) analysis and western blotting. Scanned images were digitally analysed using ImageJ and the immunomembrane plug-in. ABCB5 expression on protein level was correlated with clinical characteristics and impact on survival. ABCB5 was co-labelled with CD44 in immunohistochemical and immunofluorescence double labelling experiments. Expression subgroups were identified by receiver operating characteristics (ROC) analysis. Results: High ABCB5 expression was significantly associated with tumour progression and recurrence of the tumour. Multivariate analysis demonstrated high ABCB5 expression as an independent prognostic factor (p=0.0004). Immunohistochemical and immunofluorescence double labelling experiments revealed ABCB5 expression by CD44+ cancer cells. ABCB5 specificity was confirmed by western blot and RT-PCR analysis. Conclusions: For the first time, this study provides evidence that ABCB5 expression in OSCC might be associated with tumour formation, metastasis and a putative CSC compartment. One of the principal mechanisms for protecting putative cancer stem cells is through the expression of multifunctional efflux transporters from the ABC gene family, like ABCB5. This provides one mechanism in which putative cancer stem cells could survive and may lead to tumour relapse. Knowledge of expression profiles of ABC transporters and other genes involved in MDR will likely help therapeutic optimisation for cancer patients in clinic. However, this hypothesis requires further in vitro and in vivo studies.
Gesehen am 22.05.2018